Flow boiling heat transfer enhancement of R134a in additively manufactured minichannels with microengineered surfaces - Ye, Hanyang (2024)
Additive manufacturing (AM) of metal components has opened new frontiers in heat transfer applications owing to its wide design freedom, which enables previously unexplored geometries with enhanced thermal performance to be developed. Open minichannels, on the other hand, consist of an extra manifold situated above the common flow channels, have been demonstrated to effectively reduce pressure drop and two-phase flow instability by mitigating backflow and maldistribution. In this paper, we synergized open minichannel design methodology with an ultrascalable surface microstructuring method for AM AlSi10Mg to improve flow boiling heat transfer performance of R134a. Experiments were conducted at the refrigerant mass flow rates (ṁ) of 0.005 kg/s to 0.01 kg/s (corresponding to mass fluxes of 73 to 146 kg/m2⋅s), and effective heat fluxes (qeff) of 1.8 kW/m2 to 141 kW/m2, by supplying 2 ℃ subcooled liquid to the minichannel inlet at saturation pressure (Psat) of 7.27 bar. The effects of heat flux, nucleation site density, mass flow rate and location of nucleation sites on the harmonic-average heat transfer coefficient (have) and pressure drop (ΔP) along the flow direction are investigated and compared against a conventionally manufactured (Al6061) counterpart. Our results show that the proposed etching process significantly improves the cooling performance of AM microstrucured minichannels, resulting in 210% higher have than Al6061 with negligible pressure drop penalty. The flow visualization results reveal a sequential order of nucleation site activation with increasing heat flux for microstructured open minichannels, which starts from the top of fins, followed by the corners and other three surfaces within the channels. This also results in the non-negligible effects of mass flow rate on cooling performance for microstructured minichannels, with approximately 10%–66% higher have at the lowest mass flow rate. Besides, the pressure drop penalty resulting from plain AM rough surface is also reduced by up to 13% through the proposed microstructuring process. In all, this work not only successfully identifies the dominant mechanisms in AM microstructured open minichannels, but it also provides useful minichannel design guidelines for high-performance two-phase cooling devices by AM.